SEVERE CONSEQUENCES OF ENVIRONMENTAL PROBLEMS IN THE SURKHANDARYA REGION - Raximova Gulchehra Sobirjonovna; Mirzaxamdamova Dildora Zafarovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the state of chemical, construction materials, metalworking, chemical, nitrogen and organic fertilizers used in agriculture, oil refining industries built in 1940-80 in Surkhandarya region. The causes of changes in the ecological status of these industrial enterprises in Samarkand region, the negative impact on public health, the consequences of damage to soil, water and air in the surrounding area have been studied.